Surgical Outcomes of Primary and Revision Augmentation Rhinoplasty using a Processed Fascia Lata. Issue 2 (March 2015) - Kim, Yoo Suk; Park, Do Yang; Shin, Dong Hyun; Yang, Seok Min; Seong, Sang Yeob; Yoon, Joo-Heon; Kim, Chang-Hoon
Background: Dorsal augmentation is the most commonly performed procedure in rhinoplasty for Asian patients. Due to the anatomic features of the Asian nose, the use of nonautologous materials to obtain a proper degree of augmentation is inevitable in most cases. Because the use of nonautologous materials possesses a higher risk of complications, surgeons are concerned about selecting suitable materials for the procedure, especially in revision rhinoplasty. Therefore, this study was designed to evaluate the suitability and usefulness of a homologous material, Tutoplast-processed fascia lata (TPFL), in revision augmentation rhinoplasty. Methods: Retrospective analysis of 104 rhinoplasty patients (primary, 86; revision, 18) who had undergone dorsal augmentation using TPFL was conducted. The comparison of surgical outcomes between primary and revision surgery was made using objective [dorsal height (DH) and radix height (RH), complication rate] and subjective (patient satisfaction) parameters. Results: The degree of augmentation represented by DHand RH was comparable between primary and revision rhinoplasty using TPFL. In comparing the rate of postoperative complications, only minor incidents were noted, in six cases after primary surgery and in one case after revision surgery. Patient satisfaction was measured in both primary and revision augmentation, with a significant difference observed between the two groups (40.57 ∓ 9.25 versus 31.48 ∓ 7.59; p < 0.05). Conclusion: TPFL is a feasible implant material that delivers suitable augmentation and patient satisfaction with minimal morbidity in both primary and revision rhinoplasty.